2014
DOI: 10.1111/desc.12158
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control moderates early childhood temperament in predicting social behavior in 7‐year‐old children: an ERP study

Abstract: Behavioral inhibition (BI) is a temperament associated with heightened vigilance and fear of novelty in early childhood, and social reticence and increased risk for anxiety problems later in development. However, not all behaviorally inhibited children develop signs of anxiety. One mechanism that might contribute to the variability in developmental trajectories is the recruitment of cognitive-control resources. The current study measured N2 activation, an ERP (event-related potential) associated with cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 48 publications
13
94
0
Order By: Relevance
“…Maternal report of social fear was obtained using the Toddler Behavior Assessment Questionnaire (TBAQ; 41 ). As in previous work, measures were standardized and averaged to create a BI composite 42,43 . Combining data from different contexts, informants, and ages better reflects the child's temperament than one single measure alone.…”
Section: Methodsmentioning
confidence: 99%
“…Maternal report of social fear was obtained using the Toddler Behavior Assessment Questionnaire (TBAQ; 41 ). As in previous work, measures were standardized and averaged to create a BI composite 42,43 . Combining data from different contexts, informants, and ages better reflects the child's temperament than one single measure alone.…”
Section: Methodsmentioning
confidence: 99%
“…An ERP associated with the detection of cognitive conflict (Botvinick, Braver, Barch, Carter, & Cohen, 2001; Nieuwenhuis, et al, 2003; Van Veen & Carter, 2002) is the N2, which is usually observed at medial-frontal sites 250 to 500 ms following stimulus onset (Lahat, Todd, Mahy, Lau, & Zelazo, 2009; Lamm, Zelazo, & Lewis, 2006). In a recent study (Lamm, et al, in press), N2 amplitude was larger (i.e., more negative) during a go/no-go task for children with higher BI scores. Additionally, increased N2 was associated with continuity of temperamental shyness, which is itself associated with heightened risk for anxiety symptoms (Biederman, Rosenbaum, Chaloff, & Kagan, 1995; Schwartz, Snidman, & Kagan, 1999).…”
mentioning
confidence: 80%
“…Research (Lamm et al, in press; McDermott et al, 2009) suggests that neural responses to cognitive conflict and self-monitoring moderate the relations between BI and risk for psychopathology and response to stressful social situations. For example, adolescents with high childhood BI displayed enhanced Error Related Negativity (ERN), an event related potential (ERP) reflecting enhanced response monitoring, which moderated the relation between early BI and later anxiety problems (McDermott, et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the positive correlation between AW and standardized measures of inhibitory control can represent a risk and resiliency factor (Brooker, Kiel & Buss, 2016;Lamm et al, 2014;Valiente, Swanson & Lemery-Chalfant, 2012). For instance, emotional and behavioral regulation can help children display competence in schoolrelated activities as they are able to control impulses (Blair & Raver, 2015;McClelland et al, 2014;Montroy, Bowles, Skibbe, & Foster, 2014).…”
Section: Approaches To Learning Of Young Children Who Exhibit Higher mentioning
confidence: 99%